Creative art therapies in the treatment of adolescents with eating disorders: an integrative review and thematic network analysis - Steiner, Samantha; Dürk, Mara; Warth, Marco (The arts in psychotherapy, 2024)
Eating disorders, prevalent mental health conditions, affect between 0.1% and 3.8% of the general population and 1.1% of adolescents in Europe. Evidence suggests that the peak age of onset is 15.5 years. The recent and ongoing integration of creative art therapies into clinical settings suggest mental health benefits, and their application has been extended to different disorders and populations including eating disorders. However, there is a paucity of research focusing specifically on adolescents. Therefore, the present integrative review identified and summarized research conducted with creative art therapies in the treatment of adolescents diagnosed with an eating disorder. Additionally, a thematic network analysis facilitated the identification and mapping of relevant clinical themes. A database search in English and German, conducted according to the PRISMA 2020 guidelines, resulted in the selection of ten articles. A thematic network analysis of both qualitative (n = 7) and quantitative (n = 3) studies, allowed the extraction of six global themes: identity, relationships, empowerment, hope, re-signify and defence. Themes were explored and described individually and intertwined. Results suggested consistency of creative art therapies interventions with other psychotherapeutic approaches for the treatment of eating disorders. Furthermore, their apparent developmental appropriateness for the adolescent population and the potential for strengthening the therapeutic process were highlighted.
Online verfügbar: 29. Oktober 2024, Artikelversion: 12. November 2024
Gesehen am 13.05.2025